3D bioprinting as a future of regenerative medicine and hope for transplantology - Gładysz, Konrad; Szydłowska, Justyna; Żuchnik, Olga; Król, Olgierd; Kwiatkowski, Piotr; Kuczyńska, Beata; Czelej, Magdalena; Kłos, Aleksander; Gieroba, Krzysztof; Szydłowski, Marcin (Journal of Education, Health and Sport, 2022)
Introduction: 3D bioprinting is a continuously refined technology that enables tissue structures to be faithfully reproduced, using specially developed bioinks and 3D printers. Thanks to its versatility, it is possible to use it in regenerative medicine and transplantation, which could have a positive impact on the survival and comfort of patients with injuries and those awaiting transplantation. Aim of the study: Summarise the current state of knowledge on the use of 3D bioprinting technology in the field of regenerative medicine and transplantation, to present the extent of the method's capabilities and examples of its applications, and to outline what role it will play in the future of medicine. Methods and materials: A review of the literature available in the PubMed database and Google Scholar from the last 5 years was conducted, using the following keywords: 3d bioprinting, regenerative medicine, tissue biofabrication. Results: Significant progress has been made in the field of bioprinting and various types of tissue are now being printed and tested. Current research into the printing of skin tissue leads us to believe that in the coming years, 3D bioprinting using stem cells will make it possible to significantly improve the treatment of skin injuries. Researchers are also working on using this technology in the field of neurology and bone damage. Conclusion: The dynamic development of 3D bioprinting technology offers the hope of eliminating the main transplantation problem related to donor availability. However, the road to wider clinical application of this technology is still a long one, due to the numerous technological difficulties associated with the development of bioprinters, advanced printers and a thorough understanding of human tissue architecture. With the current intensified research in this field, it is expected that these problems will be eliminated in time and the technology will gain more interest from clinicians.